ENGLISH-DIALOGUE AS LIBERATION: ASGHAR ALI ENGINEER’S DIALOGICAL PROCESS FOR RELIGIO-CULTURAL HARMONY AND PEACE - Abdul Rehman Kaloi; Saifullah Bhutto, (Corresponding Author) (دی اسکالر)
This paper focuses on the contribution of Asghar Ali Engineer’s services, views and his methodology of liberation and emancipation of human beings from unreasonable shackles of religious restraints through dialogue, as the best method for liberation from all sorts of sufferings and troubles, with the references to modern Quranic exegesis and the traditions of the prophet Muhammad (PBUH). He contributed in praxis for the settlement of socio-religious and communal issues and had the vision to reduce the disputes and differences of such clashes through dialogue. He argues that the Quran condemns the superiority of one’s race and faith, and it determines to liberate people from injustice, oppression, and inequality. He concludes that the message of the Quran is, first, to liberate people from suffering, and second to build the good relations with other people of faiths. The Quran, according to Engineer, suggests that there is no compulsion in religion, he openly invites for dialogue to understand and respect each other to build communal, cultural and religious harmony and peaceful coexistence.